2014
DOI: 10.7314/apjcp.2014.15.21.9191
|View full text |Cite
|
Sign up to set email alerts
|

Health Locus of Control in Indonesian Women with Breast Cancer: a Comparison with Healthy Women

Abstract: Asian Pac J Cancer Prev, 15 (21), 9191-9197 IntroductionBreast cancer is a serious health condition among women worldwide. In 2008, approximately 1.38 million new cases were diagnosed and approximately 458,000 deaths were recorded both in developed and developing countries (Ferlay et al., 2010). Receiving a breast cancer diagnosis is a life threatening negative event and potentially causes considerable psychological problems. Affected women are faced with multiple stressors throughout their illness trajectory,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
2
12
1
Order By: Relevance
“…15 Thus, even though no cause-effect relationships have been established for the above variables, maintaining a good physical and psychological status after the onset of breast cancer should be considered as having complex and multifactorial causes.…”
Section: Introductionmentioning
confidence: 99%
“…15 Thus, even though no cause-effect relationships have been established for the above variables, maintaining a good physical and psychological status after the onset of breast cancer should be considered as having complex and multifactorial causes.…”
Section: Introductionmentioning
confidence: 99%
“…Locus of control is an important factor in the healing process. Thus, several works emphasize that the internal locus of control plays a positive role in the course of cancer, and is also a prerequisite for high rates of recovery (Ghislain et al, 2016); (Iskandarsyah et al, 2014); (Rautalin et al, 2018 2014) found that women with breast cancer had a higher level of external locus of control and lower rates of internal control compared to healthy women.…”
Section: Problem Statementmentioning
confidence: 99%
“…The researchers reported that the people who have strong internal health locus of control (the belief that they can control their health condition) was likely to learn self-management [ 14 ] and showed high QOL [ 15 ], self-esteem, and life satisfaction [ 16 ]. The people having cancer showed lower scores of internal health locus of control than those of healthy people [ 17 ] because they continuously experienced a fear of recurrence [ 18 ]. However the sure way to prevent cancer recurrence is not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…However the sure way to prevent cancer recurrence is not yet known. On the other hand, the scores of internal health locus of control in people with heart disease were higher than those in healthy people at comparing the two studies using the same scale for investigating internal health locus of control [ 17 , 19 ]. These mean that psychological problems can be different in the people with cancer and heart disease, even though both diseases were considered as chronic disease.…”
Section: Introductionmentioning
confidence: 99%